Restricting Back Pain and Subsequent Mobility Disability in Community‐Living Older Persons. Issue 11 (3rd November 2014) - Makris, Una E.; Fraenkel, Liana; Han, Ling; Leo‐Summers, Linda; Gill, Thomas M.
<x xml:space="preserve">Abstract</x> Objectives To evaluate the relationship between back pain severe enough to restrict activity (restricting back pain) and subsequent mobility disability in community‐living older persons. Design Prospective cohort study. Setting Greater New Haven, Connecticut. Participants Community‐living men and women aged 70 and older (n = 709). Measurements Restricting back pain and mobility disability (defined as needing help with or unable to walk one‐quarter of a mile, climb a flight of stairs, or lift and carry 10 pounds) were assessed during monthly telephone interviews for up to 159 months. The association between restricting back pain and subsequent mobility disability was evaluated using a recurrent‐events Cox model. Secondary analyses evaluated the association between restricting back pain and mobility disability for two or more consecutive months (persistent mobility disability). Additional analyses were repeated in participants without baseline mobility disability. Results The event rate for mobility disability was 7.26 per 100‐person months (95% confidence interval (CI) = 6.89–7.64). Mobility disability episodes lasted for a median of 2 months (interquartile range (IQR) 1–4). In a recurrent‐event Cox regression analysis, after adjusting for 11 covariates, restricting back pain was strongly associated with mobility disability (hazard ratio (HR) = 3.23, 95% CI = 2.87–3.64). The association was maintained when the outcome was defined as persistent mobility disability (adjusted HR = 3.63, 95% CI = 3.15–4.20) and when participants with baseline mobility disability were omitted (adjusted HR = 3.71, 95% CI = 3.22–4.28). Conclusion Restricting back pain was strongly associated with mobility disability. Interventions that prevent or ameliorate restricting back pain may be effective for reducing the burden of mobility disability in older persons.